Métodos de seleção para qualidade e panificação em trigo com pequeno volume de amostra - Meneguzzi, Cátia (2017)
The parameters most used in evaluating the industrial quality of wheat flour are obtained by viscoelastic analyzes of farinograph, alveograph, and falling number (FN). These traditional methods have a good correlation with industrial quality. However, they are expensive, difficult to implement and require lots of seed. For this reason, selection for baking quality is usually carried out in more advanced stages of breeding programs, where the amount of seeds is sufficient to carry out the tests. Therefore, it is highly desirable to use batch quality predictive tests that are inexpensive, simple to implement and require a small amount of sample. This would allow greater selection effectiveness in the early stages of breeding programs, where the greatest genetic variability is concentrated. Thus, the first study of this dissertation aimed to determine the efficacy of the alternative method of CRS (Solvent retention capacity) in different Brazilian wheat genotypes and to verify the association between CRS and the various industrial quality parameters of wheat. Seeds from VCU of 22 wheat genotypes were cultivated in 2014 at two sowing dates in four sites in southern Brazil (Abelardo Luz - SC, Cascavel - PR, Guarapuava - PR and Não Me Toque - RS). Conventional wheat quality tests were performed: alveograph, falling number, color analysis and analyzed the materials through CRS. The results demonstrate that the CRS and wheat quality parameters have a significant G x E. There was a significant mean correlation between CRS and viscoelastic analysis demonstrating that CRS can be used as a predictor of wheat quality in Brazilian wheat genotypes. The second study aimed to determine the sedimentation in SDS in different Brazilian wheat genotypes and to observe the correlation between SDS and the gluten strength parameter, assessing the efficiency of the methodology. This study was conducted using wheat seeds from experiments conducted at four sites (Abelardo Luz - SC, Cascavel - PR, Guarapuava - PR and Não Me Toque - RS) in the year 2014 during two sowing seasons. Twenty-five genotypes, including commercial strains and cultivars, were evaluated in cultivation and use value (VCU) assays. The conventional alveograph test was performed to obtain the gluten strength parameter (W) and the alternative method of SDS. The SDS parameter shows an association (r = 0.65 **) with gluten strength (W) and can be used as a predictor in the selection of wheat genotypes for wheat protein quality.